The Meaning Of ‘Fata - Wati, Agusti Sukma; Dasuki, Akhmad; Apriansyah, Ade (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2022)
The purpose of this research was to determine the meaning of ‘Fatā